Scooty girls are safe girls: risk, respectability and brand assemblages in urban India - Krishnan, S (Routledge, 2020)
Advancing an emergent scholarship on brands as having spatial and scalar effects, this paper examines the brand as an assemblage. In doing so, it focuses on youth engagement with the brandedness of motorbikes in the South Indian city of Chennai to examine in particular how brand assemblages shape gendered engagements with risk in Indian cities. Scooters and Motorbikes are important markers of ‘youth’ and middle classness in urban South Asia, representing freedom, mobility and fun. The Scooter has further been celebrated for putting women – literally and otherwise – in the driver’s seat: creating the possibility for transgression and rebellion. This article complicates this narrative, by positioning scooters and motorbikes instead as sites upon which ‘respectable’ femininities are calibrated and articulated through young women’s engagement with brands. In doing so, it unpacks the ways in which brand assemblages enliven the agency of commodities and participate in the disciplinary processes that shape gendered urban geographies of risk and respectability.